Understanding the communicative potential of Animation - Krommenhoek, Dirk (My University, 2018)
Animation is the study and art of motion; however, the separation between animation and cinematography is uncertain due to hybridized images. The aim is to discover how animation communicates effectively. This research approaches animation as a complex visual communication system by employing concepts from semiotics. Animation is analysed on a ‘mimetic to abstract’ continuum along with the consequence produced by the various configurations of the continuum. Investigating the differences in the icon offers a reflection on the ontological and modal difference between the photographic image, photorealistic image and the rule-governed transpositions of an object (degrees of arbitrary and motivation). The distinction highlights properties that are unique to ‘genuine animation’, ‘genuine cinematography’ and their hybrid state.
It is submitted for the degree of Master of Arts in Digital Arts at the University of the Witwatersrand, Johannesburg.
Keywords: Animated films; Animation (Cinematography)